Assessment of the quality of life in patients treated for colorectal cancer - Filarecka, Agnieszka; Leksowski, Łukasz; Biernacki, Maciej; Jęchorek, Michał (Journal of Education, Health and Sport, 2022)
Colorectal cancer is a common cause of death. The incidence of cancer increases every year, it is caused by better secondary prevention - screening and early stage cancer detection. The early stages of neoplasms enable the implementation of effective treatment. The method of treating colon cancer is radical treatment - surgery. The quality of life in patients with chronic diseases such as cancer is variable in each phase of the disease. The presented work aims to show the quality of life of patients on the day of admission to the hospital for the surgical treatment of colorectal cancer. The study used standardized QLQ-C30 forms with the extension of the CR29 module. Comprehensive assessment of the quality of life enables the presentation of the patient’s condition before the procedure and is the starting point for the assessment of the patient after the procedure. The studies show that patients have the lowest assessment of the overall quality of life and emotional functioning. They judge physical and mental functioning well. Symptoms related to the disease, such as abdominal pain, significantly reduce the quality of life. The presented research shows that each time before the procedure, the patient should have the quality of life assessed in order to possibly further compare the changes in the subjective assessment of the quality of life. The research shows that patients diagnosed with cancer have a low quality of life assessment and preventive measures should be implemented in the form of consultations.